2020
DOI: 10.1002/cbf.3483
|View full text |Cite
|
Sign up to set email alerts
|

Transient receptor potential vanilloid 1 promotes EGFR ubiquitination and modulates EGFR/MAPK signalling in pancreatic cancer cells

Abstract: Transient receptor potential vanilloid-1 (TRPV1) was first identified in sensory neurons, where it was suggested as a therapeutic target for pain relief. Here, we show that TRPV1 is expressed in the pancreatic cancer cell line, PANC-1; that epidermal growth factor receptor (EGFR) expression is downregulated by overexpression or agonist-induced activation of TRPV1; and conversely, that EGFR expression is increased after silencing TRPV1. Furthermore, TRPV1 overexpression inhibits cell proliferation and significa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
27
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 30 publications
(29 citation statements)
references
References 27 publications
2
27
0
Order By: Relevance
“…Recently, it has been shown that TRPV1 regulates the Epidermal Growth Factor Receptor (EGFR) in PANC-1 cell line (Huang et al, 2020). In this study, an overexpression of TRPV1 has been associated with a decrease in protein expression of EGFR in PANC-1.…”
Section: Trp Channelsmentioning
confidence: 59%
See 3 more Smart Citations
“…Recently, it has been shown that TRPV1 regulates the Epidermal Growth Factor Receptor (EGFR) in PANC-1 cell line (Huang et al, 2020). In this study, an overexpression of TRPV1 has been associated with a decrease in protein expression of EGFR in PANC-1.…”
Section: Trp Channelsmentioning
confidence: 59%
“…The membranous fractions of EGFR were reduced, while the cytoplasmic were increased compared to the control (Huang et al, 2020). This indicates that TRPV1 promotes EGFR ubiquitination and thereby a downregulation of EGFR activity, resulting in EGFR cytoplasmic translocation and degradation, which was found to be mainly through the lysosomal pathway (Huang et al, 2020). Furthermore, it was shown that TRPV1 overexpression inhibited proliferation, probably through the MAPK signaling pathway.…”
Section: Trp Channelsmentioning
confidence: 96%
See 2 more Smart Citations
“…Either the overexpression or agonist-induced activation of TRPV1 reduced the expression of epidermal growth factor receptor (EGFR), due to its ubiquitination. Additionally, TRPV1 reduced mRNA expression of two oncogenes, KRAS and AKT2 [107]. Another member of the TRPV subfamily, TRPV6, is expressed in BON-1 cell line on mRNA and protein level, and it regulates Ca 2+ levels.…”
Section: Pancreatic Cancermentioning
confidence: 97%